Effect on percolation threshold of catalytic layer: Pt/N‐Doped graphene shell onto SWCNT for ORR electrode. Issue 1 (9th November 2022) - Dechojarassri, Duangkamol; Wang, Xiaoyang; Chae, Sangwoo; Sawada, Yasuyuki; Hashimoto, Takeshi; Saito, Nagahiro
Abstract: A high‐rate oxygen reduction reaction (ORR) is necessary for polymer electrolyte membrane fuel cells (PEMFC). In this work, by using a solution plasma technique, Pt catalytic particles coated with N‐doped graphene (Pt‐NG) were effectively produced at 25°C. According to transmission electron microscope images, the average diameter of Pt particles was 4 nm, while the graphene layer thickness was less than 1 nm. A catalytic layer of Pt‐NG supported on single‐walled carbon nanotubes (Pt‐NG/SWCNT) was synthesized. Cyclic voltammetry was used to assess the ORR characteristics of Pt‐NG/SWCNT catalytic layers. Only at a density of SWCNT to solvent ratio of 0.75 mg ml −1 were the ORR peaks clearly visible. Because of the high resistivity of SWCNT layers, the ORR peaks in other ranges, 0.4 mg ml −1 to 2.0 mg ml −1, were not clearly observed. The effect of SWCNT concentration on conductivity was proven to follow the basic concept of the percolation threshold.